THE INFLUENCE OF HALAL EDUCATION AND PRODUCT LABELING ON MUSLIM CONSUMER TRUST - Rahmawatul Hasanah; Nur Fitri Hidayanti; Sahman Z (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2025)
The study analyzes the effect of halal education and product labeling on Muslim consumers' trust. The research approach used is a quantitative approach with a survey method. Data were collected through the distribution of questionnaires to 33 Muslim respondents, using purposive sampling with criteria of consumers who understand and consume halal-labeled products. The data were processed using multiple linear regression analysis with the help of SPSS. The study shows that halal product labeling has a positive and significant effect on consumer trust, while halal education has a positive but not significant effect. Consumer trust theory emphasizes the importance of information reliability and source credibility in shaping consumer beliefs, and halal labeling serves as a formal guarantee of product halalness and quality. Halal education has a positive contribution, but its influence is not significant, indicating that consumer knowledge about halal has not yet become a dominant factor. This study emphasizes the importance of the presence of halal labels, accompanied by strengthening certification mechanisms and effective communication strategies to reinforce Muslim consumers' trust.